Efficacy and safety of endoscopic duodenal stent versus endoscopic or surgical gastrojejunostomy to treat malignant gastric outlet obstruction: systematic review and meta-analysis - Krishnamoorthi, Rajesh; Bomman, Shivanand; Benias, Petros; Kozarek, Richard A.; Peetermans, Joyce A.; McMullen, Edmund; Gjata, Ornela; Irani, Shayan S. (Endoscopy International Open, 2022)
Background and study aims Malignant disease accounts for up to 80 % of gastric outlet obstruction (GOO) cases, which may be treated with duodenal self-expanding metal stents (SEMS), surgical gastrojejunostomy (GJ), and more recently endoscopic-ultrasound-guided gastroenterostomy (EUS-GE). These three treatments have not been compared head-to-head in a randomized trial.Methods We searched the Embase and MEDLINE databases for studies published January 2015−February 2021 assessing treatment of malignant GOO using duodenal SEMS, endoscopic (EUS-GE) or surgical (laparoscopic or open) GJ. Efficacy outcomes assessed included technical and clinical success rates, GOO recurrence and reintervention. Safety outcomes included procedure-related bleeding or perforation, and stent-related events for the duodenal SEMS and EUS-GE arms.Results EUS-GE had a lower rate of technical success (95.3%) than duodenal SEMS (99.4 %) or surgical GJ (99.9%) (P = 0.0048). For duodenal SEMS vs. EUS-GE vs. surgical GJ, rates of clinical success (88.9 % vs. 89.0 % vs. 92.3 % respectively, P = 0.49) were similar. EUS-GE had a lower rate of GOO recurrence based on limited data (P = 0.0036), while duodenal SEMS had a higher rate of reintervention (P = 0.041). Overall procedural complications were similar (duodenal SEMS 18.7 % vs. EUS-GE 21.9 % vs. surgical GJ 23.8 %, P = 0.32), but estimated bleeding rate was lowest (P = 0.0048) and stent occlusion rate was highest (P = 0.0002) for duodenal SEMS.Conclusions Duodenal SEMS, EUS-GE, and surgical GJ showed similar clinical efficacy for the treatment of malignant GOO. Duodenal SEMS had a lower procedure-related bleeding rate but higher rate of reintervention.